International cooperation on money laundering: the importance of direct assistance, international treaties and prevention mechanisms - Anna Carolina Canestraro (Revista Brasileira de Direito Processual Penal)
The present study aims to provide a possible response to the difficulties that the context of global crime has brought to the prosecution of money laundering in reason of an increasingly reduced control over financial flows, especially at an international level. In other words, would there be any mechanism at the disposal of the State that would allow it to do the necessary follow-the-money typical of this specific crime more efficiently and quickly? As a possible answer, the international cooperation was chosen as an important instrument of prosecution for the crime of money laundering. And based on the recommendations of Financial Action Task Force (FATF), among all the mechanisms of cooperation, direct assistance was prioritized as the most effective and swift mechanism to accompany the dynamics that demand the pursuit of this crime. In the end, is demonstrated the importance of combining mechanisms of cooperation with preventive methods, with emphasis on the Financial Intelligence Units, in order to efficiently combat this new crime.